Ready To Be A Blood Hero: Edukasi Kemanusiaan dan Gerakan Solidaritas - Sukmawati, Sukmawati; Nurhakim, Furkon; Mamuroh, Lilis; Kosim, Kosim (GUYUB: Journal of Community Engagement, 2025)
Humanitarian action is a tangible manifestation of social awareness aimed at fostering solidarity among community members. The "Ready To Be A Blood Hero" program was initiated to raise public awareness about the importance of humanitarian contributions through real actions. This program was carried out using educational and social action methods, involving the academic community of Universitas Padjadjaran and the surrounding society. A total of 270 participants registered for the event, with 216 attending. After receiving education and undergoing health screening, 159 participants were declared eligible to actively participate in this solidarity initiative. Evaluation results showed a significant increase in participants' knowledge, particularly among first-time donors, where the percentage of participants with good knowledge increased from 25% to 62.5% after the educational session. Additionally, the program successfully collected 159 units of blood, which were donated to the Blood Transfusion Unit to help meet community needs. These achievements demonstrate that proper education can effectively encourage public participation in humanitarian actions. This program is expected to serve as a sustainable model for future solidarity movements